Change in Crocin, Safranal and Picrocrocin Content and Agronomical Characters of Saffron (Crocus sativus L.) under Biological and Chemical of Phosphorous Fertilizers - Naghdi Badi H (Ph.D.); Omidi H (Ph.D.); Golzad A (M.Sc. Student); Torabi H (Ph.D.); Fotookian MH (Ph.D.) (Institue of Medicinal Plants, ACECR, 2011)
Background: Biofertilizers are an alternative to chemical fertilizers for increasing soil productivity and plant growth in sustainable agriculture. Therefore, it is necessary to determine the effects of biofertilizers on valuable medicinal plants such as saffron. Objective: To determine the effects of chemical and bio-fertilizer phosphorous on quantitative yield and major active components content of saffron (Crocus sativus L.). Methods: This study has been conducted in Absard region, north of Tehran, Iran along 2006-2008 in a randomized complete block design with three replications and four fertilizer treatments. The treatments were p1 (Control or no applying phosphorous fertilizer), p2 (150 kg/ha phosphorous as ammonium phosphate), p3 (100 gr/ha bio-fertilizer as biophosphore) and p4 (a mixture of 50 g/ha bio-fertilizer as biophosphore + 75 kg/ha phosphorous as ammonium phosphate). Results: The treatments had significant effects (p<0.01) on fresh stigma and style length, number and leaf length, saffron yield (dry weight of stigma and style), and content of safranal, crocine and picrocrocine. Although the yield of stigma and style were not different in p2 (150 kg/ha phosphorous) and p4 (a mixture of 50 g/ha bio-fertilizer as biophosphore + 75 kg/ha phosphorous as ammonium phosphate) treatment, but the application of bio-fertilizer (p3) produced the most saffron yield, addition cause efficiency about 13.77% more than chemical treatment. However, p3 (100 g/ha bio-fertilizer as biophosphore) was the best treatment in respect of picrocrocine content. Also, the maximum content of safranal and crocin was obtained in p4 (a mixture of 50 g/ha bio-fertilizer as biophosphore + 75 kg/ha chemical phosphorous as ammonium phosphate). Conclusion: Application of the chemical/bio- fertilizer increased qualitative and quantitative Yield of saffron. Also, the application of biophosphore can be in order to reduction in application of chemical phosphorous fertilizer in agro-ecosystem which is attitude toward minimizing of environmental pollution and sustainable agriculture.